Respiratory Epithelial Orbital Cyst: A Case Report and Literature Review - Sally Al Abdulmohsen; Ayman Ayoubi; Sadeq Al-Dandan (Hindawi Limited, 2018)
A 44-year-old male with schizophrenia presented with progressive right proptosis for one year and conjunctivitis for two months. An orbital cyst was seen in the superotemporal region on computerized tomography and was surgically removed. There was no history or radiological signs of paranasal sinus disease or previous trauma. Histopathologic evaluation revealed a cyst lined with respiratory epithelium. Respiratory choristomatous cysts of the orbit are considered rare in both pediatric and adult patients. We review the literature of respiratory orbital cysts and conclude that they tend to present in adults and should be considered in the differential diagnoses of orbital cysts.